Analisa Pengaruh Pendapatan, Gaya Hidup Dan Literasi Keuangan Terhadap Perilaku Keuangan Mahasiswa Universitas Pelita Bangsa - Widiyawati, Vitri; Tambunan, Parulian (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Personal finance behavior is a way of managing individual or family income sources. The management process is not easy to apply because there are several systematic steps that must be followed. However, knowledge of personal financial management is the first step to proper application when managing personal money. In this study, researchers wanted to examine the effect of income on understanding student financial behavior and student lifestyle on student personal financial behavior and financial literacy on the financial behavior of students majoring in Management at Pelita Bangsa University (H. N. Putri & Rahmi, 2019). The purpose of this study was to determine the effect of income on financial behavior decisions of Pelita Bangsa University students, to determine the effect of lifestyle on financial behavior decisions of Pelita Bangsa University students, to determine the effect of financial literacy on financial behavior decisions of Pelita Bangsa University students. This research method uses descriptive quantitative. The population of this study were students majoring in Management at Pelita Bangsa University, totaling 1000 people, the sample taken in this study amounted to 100 people. The data collection technique used a questionnaire, the data analysis used in this study was SPSS 27. The analysis methods used are Validity Test, Reliability test, Classical Assumption Test, Multiple Linear Regression Test, R-Square and Test t. The results showed that: (1) Income has a positive and significant effect on the financial behavior of Pelita Bangsa University students. (2) Lifestyle has a positive and significant effect on the financial behavior of Pelita Bangsa University students (3) Financial literacy has a positive and significant effect on the financial behavior of Pelita Bangsa University students.